Struktur Naratif Cerpen Yabu No Naka Karya Akutagawa Ryuunosuke - Renda Ika Arisya; Sri Oemiati (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2018)
Aktan is someone or something that is perfecting or undergoing action. Yabu no Naka's short story research using the Greimas act scheme aims to analyze the actions of characters in short stories using Greimas act theory. Acting scheme includes seven function actions, namely as sender, receiver, object, subject, opposant and helper. While the Greimas functional model consists of three stages: the initial situation, the transformation stage and the final situation. The seven parts of the story in Yabu no Naka's short story are discussed with an approach using a qualitative descriptive paradigm based on the act scheme theory and functional model. The results of the study show that in the seven parts of the short stories analyzed, there are 8 act schemes and 8 functional model tables. There is 1 act scheme that show zeroization (some function roles are zero or none) and 5 functional tables that show zeroization (there are zero or zero stages). Meanwhile, 7 act schemes and 3 other functional tables have a complete or perfect role.